DIDACTICS OF WORK WITH VIDEO MATERIALS IN THE PROCESS OF THE GERMAN LANGUAGE TEACHING - N.V. Rybalka (Alfred Nobel University Publisher, 2021)
The article considers the linguadidactical possibilities of using video materials in the educational process and substantiates the expediency of their use in German language classes. It is established that working with video materials mainly promotes the development of skills and abilities of listening and speaking, as well as actively contributes to the formation and further development of socio-cultural competence. The use of video in the classroom allows to individualize learning and intensify the selfdirected work of students. The introduction of video materials in the classroom also provides opportunities to create an artificial foreign language environment at any time and stage of study, adds a sense of realism, and promotes the development of audile and memory. Recently, there has been a notable increase of interest in educational videos as an effective means of teaching a foreign language, and the effectiveness of using video in German classes depends on the level of language training of students, thorough thematic selection of films and educational goals. The potential of videos is fully exploited if you integrate different activities. The most active and truly creative form of modern video work is the independent creation and viewing of video episodes. Working with video removes even a small risk of passive-receptive consumption of information, as well as increases the role of independent creative work. Preparatory explanatory conversations about the video are more useful than watching and working on the video itself, which can often only be an occasion for real communication and facilitate further understanding of the film. In addition, the effectiveness of foreign language teaching by this tool is also facilitated by the technical capabilities of video. Methodological processes based on the perception of image and sound can be used to achieve various goals of educational activities, development of creative abilities and skills through exercises for commenting and making dialogues. The use of video contributes to a more effective coverage of new language and subject material, strengthening and practical application of knowledge, the formation of receptive capabilities, executive skills and productive word use. Also, the use of video materials introduces elements of novelty, significantly expands and diversifies classes, increases cognitive activity and motivation of students, interests them in learning a particular topic and a foreign language in general.